Firm Level Effects of Offshoring of Goods and Services on Relative Labor Demand - Linda Andersson; Patrik Karpaty (Örebro University School of Business, 2012)
Based on firm level data for the Swedish manufacturing sector the objective of this paper is to analyze relative labor demand effects due to offshoring. Data allow us to distinguish between goods and service offshoring and from which country Swedish firms source their inputs. Overall, our results give no support to the fears that offshoring of goods or services lead to out-location of high-skilled activity in Swedish firms. Rather, this paper finds robust evidence that the aggregate effects from offshoring lead to increasing relative demand of high-skilled labor, mainly due to service offshoring.
Additional information: This is an extensively revised version of working paper No. 5/2007.
Keywords: F14; F16; 330; Offshoring; firm level data; relative employment; translog cost function